A utilização das TIC no ensino de Física: uma experiência no sistema prisional em Santa Maria/RS - Centenaro, Francis Jessé (2014)
This investigation concerns the inclusion of information and communication technologies in education oriented persons deprived of liberty. The objective was to examine how information technology and communication can be used as a teaching methodology, for an education that emphasizes the process of teaching and learning in the physics of the prison system, within the State Center for Youth and Adult Education and Popular Culture Julieta Balestro in Santa Maria / RS. Through qualitative methodology, case study type, activities and interviews involving information and communication technologies, with high school students the educational center located in the district of Santo Antão, at the State Penitentiary in Santa Maria were performed. The interview and the activities were planned in order to ascertain the conceptions that the student has regarding education in prisons and encourage logical thinking at the time that these physical phenomena, dealing with the experience of these situations are addressed via computer simulations and videos. It was concluded that the inclusion of information and communication technologies in the prison education improves the teaching and learning of young people and adults who are deprived of freedom, making the students involved have more interest and be able to relate to the teaching of physics their daily lives. In contrast, we detected an aggravating disregard for the universal right to education, with an overlap of duties makes most students understand the right to education as a privilege.